New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo - Tan, Ming Kai; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2017)
New taxa from the subfamily Landrevinae (Orthoptera: Gryllidae) are expected despite recent work on its taxonomy. Here, two more new species from Brunei Darussalam, Borneo are described: Duolandrevus (Eulandrevus) kawataredoki sp. nov. and Endodrelanva nympha sp. nov. The male calling song of D. (E.) kawataredoki sp. nov. is also described. We report the occurrence of a Duolandrevus (Bejorama) from Brunei close to (nr.) luzonensis Otte, 1988. We also document from Brunei a case of parasitic wasp from the genus Liris (Hymenoptera: Crabronidae: Larrini) hunting a Landrevinae.